2021
DOI: 10.3344/kjp.2021.34.3.332
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of trigeminal neuralgia: an electronic population health data study in Korea

Abstract: Background: Trigeminal neuralgia (TN) is one of the most painful disorder in the orofacial region, and many patients have suffered from this disease. For the effective management of TN, fundamental epidemiologic data related to the target population group are essential. Thus, this study was performed to clarify the epidemiological characteristics of TN in the Korean population. This is the first national study to investigate the prevalence of TN in Korean patients. Methods: From 2014 to 2018, population-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
1
14
1
Order By: Relevance
“…In the current study the TN morbidity is greater in women than in men, & it rises with years old. thirteen In line with meta-analysis by Foley et al, (12) who discovered that females outnumber men by 60.5percent, with average years old of onset of TN being 45.4 years. Also, the present study was supported by the systematic review by Zakrzewska et al, 15 who aimed to assess the clinical effectiveness of treatments in studied cases with trigeminal neuralgia & multiple sclerosis.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In the current study the TN morbidity is greater in women than in men, & it rises with years old. thirteen In line with meta-analysis by Foley et al, (12) who discovered that females outnumber men by 60.5percent, with average years old of onset of TN being 45.4 years. Also, the present study was supported by the systematic review by Zakrzewska et al, 15 who aimed to assess the clinical effectiveness of treatments in studied cases with trigeminal neuralgia & multiple sclerosis.…”
Section: Discussionmentioning
confidence: 70%
“…Surgical intervention for cure of TN is classified into 2 types: Ablation & non-ablation. 12 This potential observational research was showed in department of neurosurgery-Functional unit -Faculty of medicine Al-Azhar University from 2017 to 2021. This research was showed on twenty studied cases who were admitted & operated for Trigeminal neuralgia by different modalities according to patient age and comorbidity.…”
Section: Discussionmentioning
confidence: 97%
“…Frequency in the United States is 2.5 (males) and 5.7 (females) per 100,000 per year [18]. The incidence of TN was 100.21 per 100,000 person-years in Korea and is more common in females and the age group of 51-59 years had the highest prevalence of TN [19]. In contrast to the above frequency data, our study centre has managed only four cases of TN and three were females.…”
Section: Resultsmentioning
confidence: 99%
“…The recurring, episodic, and unpredictable clinical course of TN makes it difficult to determine the exact incidence of the disease. The estimated incidence of TN ranges from 4.3 to 26.8 per 100,000 person-years, with a lifetime prevalence of 0.03% to 0.3% [ 2 , 3 , 4 , 12 , 13 ]. Although the causes are not fully elucidated, the incidence of TN in women is higher than men, and the average age of onset is 53, with the most affected ages between 37 and 67 [ 3 , 12 , 13 , 14 , 15 ].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The estimated incidence of TN ranges from 4.3 to 26.8 per 100,000 person-years, with a lifetime prevalence of 0.03% to 0.3% [ 2 , 3 , 4 , 12 , 13 ]. Although the causes are not fully elucidated, the incidence of TN in women is higher than men, and the average age of onset is 53, with the most affected ages between 37 and 67 [ 3 , 12 , 13 , 14 , 15 ]. Most cases of TN are sporadic without apparent risk factors.…”
Section: Clinical Featuresmentioning
confidence: 99%